Impact of commercial yeast strains on wine fermentation and formation of metabolites of yellow passion fruit (Passiflora edulis Sims F. flavicarpa Degner) - Srisamatthakarn, Pattharaporn; Rauhut, Doris; Brückner, Hans; Justus Liebig University Giessen (My University, 2010)
Juice of yellow passion fruit (YPF) was fermented with different commercial yeast strains ofSaccharomyces. This research aimed to investigate the impact of one commercial strain ofSaccharomyces bayanus (Strain A) and two strains of Saccharomyces cerevisiae (Strain B andC) on the fermentation kinetics and formation of metabolites produced by wine yeast in YPFwines. The results showed that most parameters were significantly different depending on theyeast strain used. The YPF wine fermented with the A and B strain showed the most diversefermentation parameters and produced significantly higher concentrations of fatty acid ethylesters, which contribute to very pleasant odours of various fruity notes in YPF wine. However,the B strain also produced high concentrations of acetaldehyde, acetic acid and acetic acidesters in YPF wines. The C strain developed the highest amounts of lactic acid. This strain alsoproduced larger concentrations of keto acids, principally pyruvate and α-ketoglutarate, whichhave implications for wine stability and quality due to their abilities to bind sulphur dioxide.
Keywords: yeast strains; metabolites; yellow passion fruit; Passiflora edulis Sims f. flavicarpa Degner; ddc:630